2015
DOI: 10.1016/j.febslet.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional characterization of tumor suppressors TIG3 and H‐REV107

Abstract: a b s t r a c t H-REV107-like family proteins TIG3 and H-REV107 are class II tumor suppressors. Here we report that the C-terminal domains (CTDs) of TIG3 and H-REV107 can induce HeLa cell death independently. The N-terminal domain (NTD) of TIG3 enhances the cell death inducing ability of CTD, while NTD of H-REV107 plays an inhibitory role. The solution structure of TIG3 NTD is very similar to that of H-REV107 in overall fold. However, the CTD binding regions on NTD are different between TIG3 and H-REV107, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 48 publications
3
35
0
Order By: Relevance
“…This type of 2A has a conserved H-NC box, and some versions have a putative transmembrane domain (Hughes and Stanway, 2000). These 2A proteins are related to the cellular H-rev107 family, the members of which are involved in the control of cell proliferation (Tsai et al, 2009; Wei et al, 2015). In addition, the H-NC box is involved in virus replication.…”
Section: Conserved Motifs and Functions Of Parechovirus-like 2amentioning
confidence: 99%
“…This type of 2A has a conserved H-NC box, and some versions have a putative transmembrane domain (Hughes and Stanway, 2000). These 2A proteins are related to the cellular H-rev107 family, the members of which are involved in the control of cell proliferation (Tsai et al, 2009; Wei et al, 2015). In addition, the H-NC box is involved in virus replication.…”
Section: Conserved Motifs and Functions Of Parechovirus-like 2amentioning
confidence: 99%
“…20 Recently, the conserved N-terminal NlpC/P60 domain of TIG3 was also found to exhibit calcium-independent phospholipase A1/2 activity, which indicated that TIG3 might be involved in the process of phospholipid metabolism. 12,39 Interestingly, the inhibitory effect on cell survival induced by the C-terminal domain must be independent of the phospholipase A1/2 activity. 39 Based on these findings, we suspect that TIG3 may not provide the tumor-suppressing activity through the mechanism of subcellular localization, but acts as a phospholipid-metabolizing enzyme on the cellular context of GBM.…”
Section: Discussionmentioning
confidence: 99%
“…12,39 Interestingly, the inhibitory effect on cell survival induced by the C-terminal domain must be independent of the phospholipase A1/2 activity. 39 Based on these findings, we suspect that TIG3 may not provide the tumor-suppressing activity through the mechanism of subcellular localization, but acts as a phospholipid-metabolizing enzyme on the cellular context of GBM. Moreover, calcium-independent phospholipase A2 enzymes have been implicated in tumorigenesis with in vitro studies, which supports our hypothesis that TIG3 plays an oncogenic role in GBM, though the loss of TIG3 phospholipase A1/A2 activity was showed to promote breast cancer lung metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…in 2015 and showed similar folding to that of HRASLS3, although the basic structure contained four α-helices and a six-stranded antiparallel β-sheet (Fig. 2 ) [ 6 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Sequence alignment was performed using ClustalW2 [ 51 ] and structural alignment was performed for HRASLS2, HRASLS3, and HRASLS4 as described by Golczak et al in 2012 [ 3 ] and Wei et al . in 2015 [ 6 ]. The β-sheets are indicated by green arrows and α-helices are indicated by red lines
Fig 3 Homology domains within the five human HRASLS enzymes.
…”
Section: Introductionmentioning
confidence: 99%